MENGUNGKAP TANTANGAN DAN DAMPAK LITERASI KEUANGAN SYARIAH TERHADAP PARTISIPASI MASYARAKAT ACEH DALAM PERBANKAN SYARIAH: LITERATUR REVIEW - Mariana, Mariana; Ramadana, Sri Winarsih; Rahmaniar, Rahmaniar (Jurnal Sosial Humaniora Sigli, 2024)
This study aims to identify the factors affecting financial literacy in Islamic banking in Aceh and analyze its impact on community participation in Islamic banking. The method used is a literature review, collecting and analyzing relevant sources of literature. The findings indicate that financial literacy in Islamic banking in Aceh is categorized as moderate, but public understanding of Islamic banking products and principles remains limited, leading to low participation in Islamic banking. The key factors hindering financial literacy include ineffective socialization, limited access to educational materials, and the minimal role of educational institutions. To improve literacy and participation, it is recommended to implement educational programs involving educational institutions, local communities, and religious leaders, as well as training based on technology and digital media. Furthermore, enhancing the accessibility of Islamic banking services and simplifying procedures and information related to Islamic products will encourage broader community participation. With improved financial literacy, it is expected that the community will better understand the benefits of Islamic banking and actively participate in the Islamic financial system.